Metode Pendidikan Karakter dalam Meningkatkan Kedisiplinan Mahasiswa di Pesantren Mahasiswa (Pesma) KH Mas Mansur Universitas Muhammadiyah Surakarta - Mashudi Al furqon; Bambang Sumarjoko; Mohamad Ali (Jurnal Pendidikan Islam, 2022)
This research was carried out because of the researchers' interest of character education methods to improve discipline carried out at the KH Mas Mansur Student Islamic Boarding School. Character education for order to form a pious generation, disciplined and polite personality, has broad knowledge and has good character. The application of the character education method is one solution to improve discipline in special aspects of religion in the modern generation now, by creating an ideal environment. The research method used in this study is a qualitative research method with a phenomological approach. The results of the study indicate that the method of character education to improving student discipline at Pesma KH Mas Mansyur is the method of internalization, exemplary, habituation, advice, appreciation, motivation, and persuasive methods. The driving factors internally come from personal and self-awareness, externally, namely from good and disciplined friends, supportive family, conducive environment, and disciplined administrators. The inhibiting factors are the lack of religious knowledge, addiction to online games, fatigue, a lot of college assignments, campus activists, the imbalance between the Pesma environment and the environment outside Pesma, the low discipline of the management.